Positive Behavior in Action: Eating Problem and Avoiding Anxiety Problem - Nur Awwaliyah Romadhani; Citra Pangestika Putri; Ulil Abshar (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. This study aims to examine the role of positive parenting and mindful parenting in preventing eating problems and avoiding anxiety problems in children and adolescents. This study is based on the theoretical assumption that responsive and warm parent-child interactions strengthen children's self-regulation abilities, while excessive control triggers maladaptive coping mechanisms. The methodology used is qualitative through a literature study approach to ten selected scientific articles obtained from various academic databases. The results show that positive parenting and mindful parenting serve as significant protective factors that reduce the risk of emotional eating, binge eating, and avoidance behavior through increased emotional stability. Conversely, restrictive, permissive, and overprotective parenting styles are strongly correlated with increased anxiety symptoms and eating problems. This study also found that the integration of cognitive-behavioral therapy (CBT) with active parental involvement is highly effective in improving family dynamics and reducing clinical symptoms. It is concluded that comprehensive preventive strategies with an integrative approach combining positive parenting, mindful parenting, and cognitive-behavioral therapy (CBT) are the primary recommendations in efforts to prevent and manage eating disorders and anxiety in children and adolescents. Abstrak. Penelitian ini bertujuan untuk menelaah peran pengasuhan positif dan mindful parenting dalam pencegahan eating problem dan avoiding anxiety problem terhadap perilaku anak dan remaja. Kajian ini dibangun di atas asumsi teoretis bahwa interaksi orang tua dengan anak yang responsif dan hangat memperkuat kemampuan regulasi diri anak, sedangkan kontrol berlebihan memicu mekanisme koping maladaptif. Metodologi yang digunakan adalah kualitatif melalui pendekatan studi literature terhadap sepuluh artikel ilmiah terpilih yang diperoleh dari berbagai basis data akademik. Hasil penelitian menunjukkan bahwa pengasuhan positif dan mindful parenting berfungsi sebagai faktor protektif signifikan yang menurunkan risiko emotional eating, binge eating, dan perilaku menghindar (avoidance) melalui peningkatan stabilitas emosi. Sebaliknya, pola asuh restriktif, permisif, dan overprotective berkorelasi kuat dengan peningkatan gejala kecemasan dan masalah makan. Penelitian ini juga menemukan bahwa integrasi cognitive-behavioral therapy (CBT) dengan keterlibatan aktif orang tua sangat efektif dalam memperbaiki dinamika keluarga dan mereduksi gejala klinis. Disimpulkan bahwa strategi preventif yang komprehensif dengan pendekatan integratif yang mengombinasikan pengasuhan positif, mindful parenting, dan cognitive-behavioral therapy (CBT) menjadi rekomendasi utama dalam upaya pencegahan dan penanganan perilaku masalah makan dan kecemasan pada anak dan remaja.